PENGARUH PENAMBAHAN TOUGE SEBAGAI SUMBER NITROGEN TERHADAP MUTU NATA DE KAKAO - Fifendy, Mades; Putri, Dwi Hilda; Maria, Shinta Sari (IAIN Batusangkar, 2011)
The research was aimed at knowing the effect of adding touge as nitrogen source on the quality of Nata de cacao. The research design used was completely randomized design with six treatments (without nitrogen source, urea 1.5 gr., touge 175 gr, touge 200 gr, touge 225 gr, and touge 250 gr). These were done three times. The parameter tested was thickness, fiber content, and elasticity of nata de cacao. The data obtained were analyzed by using ANOVA and Extended Test BNJ with ? 5%. As the result it was shown that the adding of touge as the nitrogen source and improve the thickness and the fiber content. However the addition of touge with different concentration did not give any effect significantly. For elasticity, the higher fiber contents the chewier nata de cacao. In short, the addition of touge as a nitrogen source effect on the quality of nata de cacao, in terms of its thickness, fiber contents, and plasticity.Key words: nitrogen sources, nata de cacao, acetobacter xylinum